Song Popularity as a Contagious Process in Great Britain - Rosati, Dora P. (My University, 2015)
Determining the mechanisms by which a song becomes popular is a complex problem. The rapidity with which some songs gain popularity often leads to them being described as 'contagious' or 'infectious'. Upon closer examination, we find that the download time series for many popular songs do resemble epidemic curves derived from case report data for infectious diseases. This correspondence suggests an interesting link between the fields of infectious disease research and music research: perhaps ideas from epidemiological modelling might be useful in investigating how certain songs 'spread' through human populations, and perhaps employing disease epidemic models might help to better understand the mechanisms underlying song popularity. Download data were obtained from MixRadio based on song downloads through Nokia cell phones in Great Britain over a seven year period and aggregated at various timescales. Songs were characterized by fitting a standard epidemic model to song download time series. The fits estimate standard epidemiological parameter values for each song, providing new insights about popularity of music. In addition, we propose and analyze a new model that is better suited to 'song transmission' and comment on how this model might be used to study song popularity in the future.